2016
DOI: 10.1016/j.trsl.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of human alloreactive T cells by linear tetrapyrroles; relevance for transplantation

Abstract: The main limitation to successful transplantation is the antigraft response developed by the recipient immune system, and the adverse side effects of immunosuppressive agents which are associated with significant toxicity and counter indications such as infection and cancer. Furthermore, immunosuppressants do little to prevent ischemia-reperfusion injury during the transplantation procedure itself hence there is a growing need to develop novel immunosuppressive drugs specifically aimed at prolonging graft surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Additionally, a recent in vitro study reports that proinflammatory cytokine production, including GM-CSF, is downregulated by BV and phycocyanobilin (PCB; an algal linear tetrapyrrole structurally similar to BV) pre-treatment of human peripheral blood mononuclear cells (PBMC) stimulated by a mixed lymphocyte reaction. (49) These data agree with recent reports that BV and enzymes involved in bile pigment metabolism (BVR/Haem Oxygenase-1) inhibit sterile inflammatory responses. For example, BV treatment protects rats from acetaminophen-induced toxicity (50) , ameliorates cerebral ischemia reperfusion injury in rats (51) and supresses inflammatory cytokine release in ischemia reperfusion injury and insulin resistance models.…”
Section: Inflammatory Cytokinessupporting
confidence: 92%
“…Additionally, a recent in vitro study reports that proinflammatory cytokine production, including GM-CSF, is downregulated by BV and phycocyanobilin (PCB; an algal linear tetrapyrrole structurally similar to BV) pre-treatment of human peripheral blood mononuclear cells (PBMC) stimulated by a mixed lymphocyte reaction. (49) These data agree with recent reports that BV and enzymes involved in bile pigment metabolism (BVR/Haem Oxygenase-1) inhibit sterile inflammatory responses. For example, BV treatment protects rats from acetaminophen-induced toxicity (50) , ameliorates cerebral ischemia reperfusion injury in rats (51) and supresses inflammatory cytokine release in ischemia reperfusion injury and insulin resistance models.…”
Section: Inflammatory Cytokinessupporting
confidence: 92%
“…We have previously reported that the HO-1 reaction product, biliverdin, reduces DC maturation marker expression and pro-inflammatory cytokine production 40 . We therefore hypothesised that biliverdin may be mediating the effect of carnosol/curcumin-induced HO-1.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, HIF1α, which is expressed highly in lung biopsies from patients with pulmonary TB, is necessary for MMP-1 gene expression and secretion ( 184 ). Moreover, HIF1α, and DFX, has been shown to positively regulate transcript levels of heme oxygenase−1 (HO-1), an oxidative stress response protein that catalyzes the degradation of heme to Fe 2+ and other intermediaries ( 185 , 186 ). HO-1 expression is also markedly increased in rabbits, mice, and non-human primates during experimental Mtb Erdman and Mtb H37Rv infection and its expression gradually decreases during subsequent successful therapy ( 187 ).…”
Section: Fine-tuning Hif1α and Iron; A Mechanism To Support Innate Homentioning
confidence: 99%